The Prehospital Evaluation and Care of Moderate/Severe TBI in the Austere Environment. (19th February 2020) - Gurney, Jennifer M; Loos, Paul E; Prins, Mayumi; Van Wyck, David W; McCafferty, Randall R; Marion, Donald W
Abstract: Increased resource constraints secondary to a smaller medical footprint, prolonged evacuation times, or overwhelming casualty volumes all increase the challenges of effective management of traumatic brain injury (TBI) in the austere environment. Prehospital providers are responsible for the battlefield recognition and initial management of TBI. As such, targeted education is critical to efficient injury recognition, promoting both provider readiness and improved patient outcomes. When austere conditions limit or prevent definitive treatment, a comprehensive understanding of TBI pathophysiology can help inform acute care and enhance prevention of secondary brain injury. Field deployable, noninvasive TBI assessment and monitoring devices are urgently needed and are currently undergoing clinical evaluation. Evidence shows that the assessment, monitoring, and treatment in the first few hours and days after injury should focus on the preservation of cerebral perfusion and oxygenation. For cases where medical management is inadequate (eg, evidence of an enlarging intracranial hematoma), guidelines have been developed for the performance of cranial surgery by nonneurosurgeons. TBI management in the austere environment will continue to be a challenge, but research focused on improving evidence-based monitoring and therapeutic interventions can help to mitigate some of these challenges and improve patient outcomes.